Application of Lokal Wisdom Society in Rehabilitating River Erosion at Kenegerian Rumbio Kabupaten Kampar - Arman, Arman; Sujianto, Sujianto; Zulkifli, Zulkifli (Fakultas Perikanan dan Kelautan Universitas Riau, 2018)
Research on the application of local wisdom in rehabilitating river erosion was carriedout in Kenegerian Rumbio Kampar District from February to December 2017. The aimof this research is know the forms implementation of local wisdom to rehabilitate rivererosion, identifying factors that are inhibiting in rehabilitating river erosion, identifyingfactors that are inhibiting in rehabilitating river erosion, as well identifying and evaluating effort made in overcoming the obstacles of river erosion rehabilitation atKenegerian Rumbio Kabupaten Kampar. Results of research local wisdom is obtained1) effort rehabilitation of river erosion has been implemented, because it has been rundown hereditary by the community and in its application is done by vegetative methodand civil engineering method, 2) factors resistor there are 4, hat is household waste dumped into the river, replacement of river bank vegetation with economical vegetationdue to the change of mindset, mining activities, and land clearing In river banks, and 3) efforts undertaken to overcome the obstacles of river erosion rehabilitation shall be sanctioned to the violator custom rulesand villages such as: verbal reprimands, ostracism from society, and sanctions are not served in the affairs of Kenegerian Rumbio community.